IMPACT ANALYSIS OF MARKETING STRATEGIES THROUGH ONLINE MEDIA ON NON-TAX STATE REVENUE ACHIEVEMENTS (CASE STUDY OF CENTER FOR STANDARDIZATION AND INDUSTRIAL SERVICES HANDICRAFTS AND BATIK) - Juwarso Juwarso; Muinah Fadhilah (INFOKUM, 2022)
This research aims to determine the impact of online media marketing strategies at The Center for Standardization and Services of Crafts and Batik Industry on PNBP achievement from 2020 to 2022. The research method used is quantitative, and the data sources were obtained from the Public Service Report and Information Service Optimization Report of BBSPJIKB in 2020-2022. The data collection technique was done by counting the number of service promotions on online media and the PNBP achievement during the three years. The online media used in this study were Zoom and Instagram social media platforms. The data was analyzed and interpreted descriptively. The results of this study indicate that the promotion of BBSPJIKB services through online media from 2020-2022 did not have an impact on the PNBP achievement, as reflected by the continuous increase in PNBP achievement from 2020-2022 despite the declining trend of service promotions through online media.